Live Imaging of Inorganic Phosphate in Plants with Cellular and Subcellular Resolution. Issue 3 (26th January 2015) - Mukherjee, Pallavi; Banerjee, Swayoma; Wheeler, Amanda; Ratliff, Lyndsay A.; Irigoyen, Sonia; Garcia, L. Rene; Lockless, Steve W.; Versaw, Wayne K.
Abstract : Genetically encoded sensors enable dynamic monitoring of phosphate concentrations in cells and cell compartments of live plants. Abstract: Despite variable and often scarce supplies of inorganic phosphate (Pi ) from soils, plants must distribute appropriate amounts of Pi to each cell and subcellular compartment to sustain essential metabolic activities. The ability to monitor Pi dynamics with subcellular resolution in live plants is, therefore, critical for understanding how this essential nutrient is acquired, mobilized, recycled, and stored. Fluorescence indicator protein for inorganic phosphate (FLIPPi) sensors are genetically encoded fluorescence resonance energy transfer-based sensors that have been used to monitor Pi dynamics in cultured animal cells. Here, we present a series of Pi sensors optimized for use in plants. Substitution of the enhanced yellow fluorescent protein component of a FLIPPi sensor with a circularly permuted version of Venus enhanced sensor dynamic range nearly 2.5-fold. The resulting circularly permuted FLIPPi sensor was subjected to a high-efficiency mutagenesis strategy that relied on statistical coupling analysis to identify regions of the protein likely to influence Pi affinity. A series of affinity mutants was selected with dissociation constant values of 0.08 to 11 mm, which span the range for most plant cell compartments. The sensors were expressed in Arabidopsis ( Arabidopsis thaliana ), and ratiometric imaging was used to monitor cytosolic Pi dynamics in root cells in response to Pi deprivation and resupply. Moreover, plastid-targeted versions of the sensors expressed in the wild type and a mutant lacking the PHOSPHATE TRANSPORT4;2 plastidic Pi transporter confirmed a physiological role for this transporter in Pi export from root plastids. These circularly permuted FLIPPi sensors, therefore, enable detailed analysis of Pi dynamics with subcellular resolution in live plants.